Development and validation of UPLC-UV method for the determination of rubraxanthone in human plasma - Meri Susanti; Yahdiana Harahap; Afrizal Itam; Dachriyanus (GarVal Editorial Ltda., 2019)
Context: Rubraxanthone has potential health benefits, such as antioxidant, anti-bacterial and cytotoxic agent. A sensitive method is required to quantify plasma concentrations to assess its efficacy. Aims: To develop and validate an analytical method for the determination rubraxanthone in human plasma using ultra-performance liquid chromatography (UPLC-UV) for pharmacokinetic application. Methods: Chromatographic separation was performed aced using a C18 column (100 mm × 3.0 mm, particle size 1.8 μm) with a mobile phase consisting of acetonitrile - 0.4% formic acid (75:25, v/v). The isocratic flow rate was 0.3 mL/min with elution time for rubraxanthone was approximately 3 min and UV detection were at 243 nm. Biological sample preparation involved protein precipitation method with acetonitrile. The developed method was validated as EMEA guidelines for its selectivity, linearity, sensitivity, precision, accuracy, recovery and stability. Results: The method was proven to be linear over a plasma rubraxanthone concentration range of 206 to 6180 ng/mL with a mean correlation coefficient of 0.999. The within-run and between-run precision (coefficient of variation) were less than 4.7%. The mean recovery of rubraxanthone from human plasma was found to be greater than 95%. The lower limits of quantitation of the method was determined to be 206 ng/mL. The samples remained stable during the processing and analysis times and also during the three freeze/thaw cycles. Conclusions: The UPLC-UV method was validated for all of the criteria that were necessary for a bioanalytical method and could reliably quantitate rubraxanthone in human plasma for future clinical pharmacokinetic study.